On mixed-integer optimal control with constrained total variation of the integer control - Sebastian Sager; Clemens Zeile (Computational Optimization and Applications, 2020)
The combinatorial integral approximation (CIA) decomposition suggests solving mixed-integer optimal control problems by solving one continuous nonlinear control problem and one mixed-integer linear program (MILP). Unrealistic frequent switching can be avoided by adding a constraint on the total variation to the MILP. Within this work, we present a fast heuristic way to solve this CIA problem and investigate in which situations optimality of the constructed feasible solution is guaranteed. In the second part of this article, we show tight bounds on the integrality gap between a relaxed continuous control trajectory and an integer feasible one in the case of two controls. Finally, we present numerical experiments to highlight the proposed algorithm's advantages in terms of run time and solution quality.
Keywords: M20; M27; B35; C11; C59; 510; Mixed-integer linear programming; Optimal control; Discrete approximations; Switched dynamic systems; Approximation methods and heuristics